What do physical therapists think about evidence-based practice? A systematic review. Issue 3 (June 2015) - Mota da Silva, Tatiane; da Cunha Menezes Costa, Lucíola; Garcia, Alessandra Narciso; Costa, Leonardo Oliveira Pena
Abstract Evidence-Based Practice (EBP) has been widely implemented in different health-related areas. Several studies investigated important characteristics in EBP by physiotherapists and systematic review is needed. Therefore the aim of this study is to describe the current evidence on EBP knowledge, skills, behaviour, opinions and barriers by physiotherapists. Searches were conducted on MEDLINE, EMBASE, CINAHL, PSYCINFO, LILACS, and SciELO in September 2014. We retrieved quantitative cross-sectional studies that investigated EBP knowledge, skills, behaviour, opinions, and barriers in physiotherapy. Risk of bias was assessed using a scale to evaluate representativeness of the sample, response rate, the accuracy of the data, evidence of power calculation and the instrument used. The search yielded 12, 392 potentially eligible studies. Of these, 12 studies were included in the review (pooled sample = 6411 participants). In 3 studies that analysed knowledge, approximately 21–82% of respondents claimed to have received prior information on EBP. In 2 studies that reported skills and behaviour, nearly half of the sample had used databases to support clinical decision-making. In 6 studies that investigated opinions, the majority of the samples considered EBP necessary or important. The barriers most frequently reported were: lack of time, inability to understand statistics, lack of support from employer, lack of resources, lack of interest and lack of generalisation of results. Although the majority of physiotherapists have a positive opinion about EBP, they consider that they need to improve their knowledge, skills and behaviour towards EBP. They also faced barriers that might hinder the implementation of EBP.